Omadacycline in the treatment of severe Q fever pneumonia during an influenza epidemic: a case report with literature review - Nie, Chuanhua; Zhu, Yuan; Zhou, Huajuan; Zhu, Xinmin; Hu, Shaohua; Zhao, Xiaoli; Zhong, Xiaohua; Qian, Fengfei; Yu, Miao; Jiang, Qiuting (Frontiers in Medicine, 2025)
Q fever, caused by Coxiella burnetii (Q fever rickettsiae), is a zoonotic disease with a natural reservoir and has been reported in many countries and regions. Its clinical presentation is non-specific and easily confused with other infectious or non-infectious diseases. Conventional diagnostic methods, such as respiratory specimen culture, often fail to yield conclusive results, increasing the risk of misdiagnosis. This case involves a 78-year-old male patient from Zhejiang Province, China, who presented with fever as the primary complaint and developed severe pneumonia. The diagnosis of H1N1 influenza co-infection with Coxiella burnetii was confirmed by bronchoalveolar lavage fluid targeted high-throughput sequencing (tNGS). Following antiviral treatment with Maraviroc and antibiotic therapy with omadacycline tosilate (a novel tetracycline-class drug) for Coxiella burnetii infection, the patient’s clinical symptoms improved, biochemical markers normalized, and pulmonary imaging showed resolution. This case highlights the potential of tNGS to improve the detection rate of mixed infections in cases of severe pneumonia of unknown etiology. The novel tetracycline drug, such as omadacycline, has demonstrated efficacy against Q fever rickettsial pneumonia, offering a new perspective for clinical diagnosis and treatment.